Influence of access to a browse grove by sheep on animal nutrition and nutrient cycling - Sangare, M.; Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Pandey, V.S. (Institut de Medecine Tropicale Prince, 2002)
The influence of 0, 60 or 120 minutes of access to a grove of either Ziziphus mauritiana (Ziziphus) or Combretum aculeatum (Combretum) on forage intake and digestibility, animal growth and nutrient excretion was determined using forty intact Oudah sheep grazing for 7 h day-1 on poor quality dry season. At the same time, the effects of browse species (Combretum aculeatum and Ziziphus mauriflana) and browsing duration (0, 30, 60 et 120 min.) on in-sacco roughage degradability and rumen ammonia level (NH3-N) were also evaluated using eight mature rumen fistulated sheep. Compared to the control, Ziziphus increased both total DOM (g kg-1 LW 0.75) and total DM (g kg-1 LW) intake without decreasing herbage intake. Combretum (18 % and 29 % of total dry matter intake) reduced herbage intake. The digestibility of the diet was highest in the control and decreased linearly (P < 0.05) with access time to the groves. Despite the provision of 56 and 50 % more N than in control diet, rumen NH3-N decreased 24 h after browsing, and roughage degradability in-sacco tended to decrease in browsing sheep. Lower LWG of sheep browsing Combretum compared to control and to sheep browsing Ziziphus, may indicate the presence of anti-nutritional compounds at least in Combretum. Ziziphus increased faecal N with an even distribution in soluble and insoluble fiber bound N. Whereas, urinary N, more susceptible to volatilization, represented 36 to 50% of N excreted daily by sheep browsing Combretum, and about 70 % faecal N was in soluble form. Ziziphus revealed more potential than Combretum to increase sheep production and to reduce N losses in low input crop/livestock systems.